Revolusi Hijau: Otomatisasi Baterai dalam Energi Surya - Kiswantono, Agus; Nur Wahib, Puji (Fakultas Teknik Universitas Bhayangkara Surabaya, 2024)
ABSTRACT This research investigates a battery charging system using renewable energy with the help of a buck converter, which functions to step down the voltage from the renewable energy source to a level suitable for the battery. The test results show that the battery charging voltage remains stable between 12.5 to 13.8 volts during 3 days of charging. The buck converter plays a crucial role in maintaining charging efficiency by dynamically adjusting the voltage and current according to the battery's needs. The system also maintains good stability, with automatic monitoring that adjusts the charging process based on fluctuations in solar intensity. The sustainability of the system is achieved through the use of solar energy, reducing reliance on fossil fuels. The automation of the charging process allows the system to operate independently without human intervention, enhancing efficiency and convenience. Thus, this system is not only efficient and stable but also supports the more sustainable and environmentally friendly use of renewable energy. Keywords: Renewable energy, battery charging system, buck converter, voltage stability, solar energy ABSTRAK Penelitian ini mengkaji sistem pengisian baterai menggunakan energi terbarukan dengan bantuan buck converter, yang berfungsi untuk menurunkan tegangan dari sumber energi terbarukan ke level yang sesuai untuk baterai. Hasil pengujian menunjukkan bahwa tegangan pengisian baterai tetap stabil antara 12,5 hingga 13,8 volt selama 3 hari pengisian. Buck converter berperan penting dalam menjaga efisiensi pengisian dengan menyesuaikan tegangan dan arus secara dinamis sesuai kebutuhan baterai. Sistem ini juga mempertahankan stabilitas yang baik, dengan pemantauan otomatis yang menyesuaikan pengisian berdasarkan fluktuasi intensitas sinar matahari. Keberlanjutan sistem tercapai melalui pemanfaatan energi surya yang ramah lingkungan, mengurangi ketergantungan pada energi fosil. Otomatisasi pengisian memungkinkan sistem berjalan secara mandiri tanpa intervensi manusia, meningkatkan efisiensi dan kenyamanan. Dengan demikian, sistem ini tidak hanya efisien dan stabil, tetapi juga mendukung penggunaan energi terbarukan yang lebih berkelanjutan dan ramah lingkungan. Kata kunci: Energi terbarukan, sistem pengisian baterai, buck converter, kestabilan tegangan, energi surya